2021
DOI: 10.2147/jir.s342545
|View full text |Cite
|
Sign up to set email alerts
|

Th1/Th2 Balance in Young Subjects: Relationship with Cytokine Levels and Metabolic Profile

Abstract: Purpose:We aim to identify Th1 and Th2 cell clusters in young subjects, including their clinical and metabolic characteristics and the Th1/Th2 balance. Patients and Methods: A total of 100 participants were included. The frequencies of Th1 and Th2 cells in peripheral blood were determined by flow cytometry. Serum C-reactive protein was measured using a turbidimetric assay, and insulin levels were quantified with an enzyme-linked immunosorbent assay. Circulating cytokine levels were analyzed using a multiplex s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 63 publications
(94 reference statements)
4
15
0
Order By: Relevance
“…Higher proportions of CD4+ Th cells in PBMC were also observed in obese subjects (BMI > 35) compared to lean controls ( 33 ). In addition to obesity, factors such as hyperglycemia, dyslipidemia and insulin resistance have been shown to further modulate circulating T cell subtypes by increasing the ratio of Th1 to Th2 cells ( 34 ). Recent findings from our group also demonstrated that hyperglycemia in obesity and type 2 diabetes leads to an increased proportion of activated Th cells (expressing CD278), cytotoxic T cells as well as inflammatory monocytes (CD14+CRTh2+) in PBMC compared to individuals with obesity that are metabolically healthy ( 4 ).…”
Section: Understanding Of Immune Dysfunction In the Context Of Obesitymentioning
confidence: 99%
“…Higher proportions of CD4+ Th cells in PBMC were also observed in obese subjects (BMI > 35) compared to lean controls ( 33 ). In addition to obesity, factors such as hyperglycemia, dyslipidemia and insulin resistance have been shown to further modulate circulating T cell subtypes by increasing the ratio of Th1 to Th2 cells ( 34 ). Recent findings from our group also demonstrated that hyperglycemia in obesity and type 2 diabetes leads to an increased proportion of activated Th cells (expressing CD278), cytotoxic T cells as well as inflammatory monocytes (CD14+CRTh2+) in PBMC compared to individuals with obesity that are metabolically healthy ( 4 ).…”
Section: Understanding Of Immune Dysfunction In the Context Of Obesitymentioning
confidence: 99%
“…The meta-analysis showed there was a higher percentage of Th2 cells in patients than HCs (SMD = 0.62; 95% CI = 0.03, 1.20; p = 0.04; n = 8; Figure 2 ). Sensitivity analysis that excluded the Yong Wang study ( Wang et al, 2006 ) and the Yanni Jiang study ( Matia-Garcia et al, 2021 ) reduced the heterogeneity of these results (I 2 = 2.22%; Supplementary Figure S2 ), and the percentage of Th2 cells remained higher in patients than HCs (SMD = 0.29; 95% CI = 0.03, 0.56; p = 0.03; n = 6).…”
Section: Resultsmentioning
confidence: 99%
“…Although many studies have examined the levels of Th1 and Th2 cells in patients with SLE, many of these results are discordant ( Viallard et al, 1999 ; Amit et al, 2000 ; Li et al, 2002a ; Oster et al, 2019 ). Thus, examination of changes in the levels of Th1 and Th2 cells during SLE is an active area of research ( Matia-Garcia et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In general, there is an upregulation of both Th1 and Th17 profiles, including their characteristic cytokines, while Th2 and Treg profiles and their cytokines are downregulated in obesity. 122 , 123 , 124 , 125 The Treg/Th17 ratio is decreased in obesity, and this is related to metabolic health. 126 , 127 Severe COVID‐19, in turn, provokes dampened Th1 and Treg responses, while promoting the Th17 profile.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these results, an important feature that was largely overlooked in the studies is the further characterization of the subsets of lymphocytes beyond CD4 + T cells. In general, there is an upregulation of both Th1 and Th17 profiles, including their characteristic cytokines, while Th2 and Treg profiles and their cytokines are downregulated in obesity 122–125 . The Treg/Th17 ratio is decreased in obesity, and this is related to metabolic health 126,127 .…”
Section: Discussionmentioning
confidence: 99%